Effects of vitrified cryopreservation duration on IVF and neonatal outcomes - Yuling Mao; Ni Tang; Yanfen Luo; Ping Yin; Lei Li (Journal of Ovarian Research, 2022)
Abstract Background In this study, we aimed to evaluate the impact of the duration of cryopreservation storage on embryo viability, implantation competence, pregnancy outcome and neonatal outcomes. Methods We retrospectively evaluated the outcomes of patients who underwent IVF with vitrified cryopreserved embryos between January 2004 and August 2019 by following the first frozen embryo transfer cycles within the study period. A total of 31,143 patients met the inclusion criteria and were grouped according to the embryo storage time as follows: Group 1 (n = 20,926),1–90 days; Group 2 (n = 6,472), 91–180 days; Group 3 (n = 2,237), 181–365 days; Group 4 (n = 746), 366–730 days; and Group 5 (n = 762), > 731 days. Results The embryo survival rate decreased significantly with longer durations of cryopreservation. The highest and lowest survival rate was recorded in Group 1 and Group 5, respectively (34853/35338; 98.63% vs. 1281/1801; 71.13%; P < 0.01). The human chorionic gonadotropin (HCG) detection and clinical pregnancy rate was highest in Group 1 (57.85% and 55. 26%, respectively; P < 0.01). Short-term cryopreservation (≤ 3 months) is associated with higher rates of clinical pregnancy. There were no significant differences in neonatal birth weight, neonatal height and congenital anomalies among the groups (P > 0. 05). Conclusion The prolonged storage time of vitrified embryos negatively affected survival rate and clinical pregnancy rate. It did not have a significant influence on neonatal health. This study provides new findings about the relationship between prolonged storage time of vitrified embryos and clinical outcomes and offers evidence for the safety of using long-stored embryos after vitrification.